Design and Fabrication of Hollow-Core Photonic Crystal Fiber sensor For Different Edible Oils - Qanbar, Batoul H.; Ahmad, Ahmad K. (Al-Nahrain Journal for Engineering Sciences, 2025)
In this work, a sensor for cooking oils was designed and fabricated for the first time using hollow-core photonic crystal fiber (HC-PCF). This sensor was studied practically, and the results showed a difference in sensitivity depending on the type of oil. The results showed that the wavelength shift occurred with very small changes in the refractive index of the edible oil. The confinement loss was computed. Seven oils with various refractive indices were utilized. Based on our results, the relative sensitivity to various kinds of Canola oil, Sunflower oil, Olive oil, Walnut oil, Sesame oil, Corn oil, and Wheat oil are 79.9321%, 80.1588%, 77.4523%, 77.4889%, and 77.5650%, 77.6652%, 80.5902% respectively. Moreover, the proposed sensor also has low confinement losses of 6.473×10-9dB/m, 1.158×10-9dB/m, 1.2×10-9dB/m, 1.20×10-9dB/m, 1.199×10-9 dB/m, 1.2×10-9dB/m, and 6.347×10-9dB/m respectively. This sensor can be used to measure the quality of oils and distinguish their types, and they can be a practical element in oil detection systems, which will bring about a change in the future in oil detection methods.